2015
DOI: 10.46743/2160-3715/2013.1554
|View full text |Cite
|
Sign up to set email alerts
|

Teachers of Color Creating and Recreating Identities in Suburban Schools

Abstract: In this qualitative study, I explored the socialization experiences of eight teachers in two suburban high schools, and how they described their in - school identities. The findings from the study revealed how the participants constructed their identities differently for reasons that included wanting to deflect particular stereotypic images of their cultural/ethnic group or mitigating their own discomfort in revealing more private aspects of their core identities. The study offers implications for teacher educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…These findings mirror what V. Lee (2015) and Bettini et al (2021) found in terms of how Teachers of Color are not socialized to bring their whole identities into their predominantly white workspaces and the resulting discomfort and dissonance they feel. My findings also extend upon these findings by showing that when this discomfort is addressed directly and channeled into classroom DEI work, it can have powerful impacts for both Teachers of Color and their children.…”
Section: Research Question 2: How Do the Racialized Experiences Of Ki...supporting
confidence: 78%
See 4 more Smart Citations
“…These findings mirror what V. Lee (2015) and Bettini et al (2021) found in terms of how Teachers of Color are not socialized to bring their whole identities into their predominantly white workspaces and the resulting discomfort and dissonance they feel. My findings also extend upon these findings by showing that when this discomfort is addressed directly and channeled into classroom DEI work, it can have powerful impacts for both Teachers of Color and their children.…”
Section: Research Question 2: How Do the Racialized Experiences Of Ki...supporting
confidence: 78%
“…Thus far, the review of the literature has shown how research on DEI practices at independent schools could benefit from an examination of kindergarten teachers' and their (Gay, 1999;Sleeter, 1996) and the processes in which and how their identities have been expressed have always been done so with an acute awareness of how others have perceived them (Braunstein et al, 2021). Then, this subsection proceeds with a review of the literature illuminating what specific factors Teachers of Color have considered when constructing their in-school identities (Burant et al, 2002;V. Lee, 2015;Mabokela & Madsen, 2003), further highlighting how Teachers of Color have rarely, if ever, felt like they could bring their whole authentic selves into their work (Bettini et al, 2021) Researchers such as Gay (1999) and Sleeter (1996) have theorized different processes and practices Teachers of Color have undergone as they have constructed and reconstructed their identities in their schools.…”
Section: Negotiating Multiple Identitiesmentioning
confidence: 99%
See 3 more Smart Citations